Novas dimensões constitutivas do devido contraditório no processo penal contemporâneo - Durigon, Luís Gustavo (2016)
This bibliographical research, which was conducted using the deductive method, proposes a new reading of the contradictory to the Brazilian criminal proceedings in contemporary times. This study was originated from the need for punitive functional logic inversion of the criminal process as a first step towards the emancipation of the contradictory, in so far as how it is structured representing more a blind spot of the criminal proceedings than a means of information and reaction to an accusatory diffuse power and of languishing. The criminal process has diffuse micro-powers that, paradoxically, should be tensioned, repelled and contained, causing the contradictory to remain submissive to a fascist procedural structure that prevents their criminal procedure identity. One of the bases of this problem is due to the fact that the contradictory have been structured in an infraconstitucional plan from the general theory of process optic, based on an eminently civility array, whose need for disruption is essential to get the contents of the contradictory foundation and its new legal functionality. In the complex phenomenological relation of power established in the criminal proceedings, it is necessary to observe variations and contradictory connections beyond what Fazzalari had sought as an ideal process model. In this context, the genealogy of the contradictory was taking into consideration and the legal-political criminal system as a way to map not only the contradictory, as a blind spot of the Brazilian criminal process, but also creating mechanisms for the identification of (in) finite other legal territories vents. As serious as the submission of the contradictory to its own procedure is its submission in the legal extremes, being correct that in the neo-inquisitorial system, whose authoritarian inflows are far beyond the process, which allows a fertile ground for the invasion of the punitive populism, structured under the criminal common sense. Concealing a love to the criminal power, the legal system allows a template that is satisfied with the mere "respect to the contradictory", which is not other but its own denial. To enhance the contradictory, ridding it from inquisitorial claws and dogmatic layers that have been historically haunting it, it was realized the need for better structure two new dimensions of the activity: evidence and decision. Thus, revealing new ingredients of its material content and its legal functionality, and establishing an adequate epistemic criterion and indispensable in the proof formation. This should route not only the preliminary investigation and its new investigative technologies, as the entire built procedure into a complete and absolute contradictory, under the vigilance of the nullities. In addition, the construction of the provision needs to go through the participation of all legal actors in a systematic way, which meets the established dialectic in the procedure by a polycentric legal relationship. The contradictory is beyond the information and reaction, being based on the right to freedom, while its functionality is the ability to produce doubt, feeding democraticity of the criminal process in contemporary times.